Dietary patterns are associated with the prevalence of alexithymia. Issue 4 (21st June 2017) - Honkalampi, Kirsi; Ruusunen, Anu; Viinamäki, Heimo; Koivumaa‐Honkanen, Heli; Valkonen‐Korhonen, Minna; Lehto, Soili M.
Abstract : Recent evidence supports the association between healthy dietary patterns and a reduced risk of depression. The objective was: (1) to examine the associations between dietary patterns and alexithymic features; and (2) investigate whether these possible associations are explained by depressive symptoms in a cross‐sectional study among the Finnish general population aged 25–65 years. The study population was a part of the population‐based Kuopio Depression Study (KUDEP) conducted in central‐eastern Finland (n = 1747). Dietary data were collected using a food frequency questionnaire and dietary patterns from 22 predefined food groups, which were extracted by factor analysis. Alexithymia was assessed using the 20‐item Toronto Alexithymia Scale (TAS‐20) and depression using the 21‐item Beck Depression Inventory (BDI‐21). Altogether, 173 of the study subjects (9.9%) were alexithymic. Three dietary patterns were identified: "prudent, " "Western" and "traditional." Lower scores for a healthy prudent dietary pattern and higher scores for an unhealthy Western dietary pattern were associated with an increased likelihood of belonging to the alexithymic group among subjects with elevated depressive symptoms. Among subjects without depressive symptoms, alexithymia was associated with lower scores in the prudent dietary pattern, but also with higher scores in the traditional dietary pattern. General population subjects with alexithymic features may have unhealthier dietary patterns than non‐alexithymic subjects.